Simulation of forest harvesting alternative processes and concept design of an innovative skidding winch focused on productivity improvement - Di Gironimo, Giuseppe; Balsamo, Alessio; Esposito, Gianpiero; Lanzotti, Antonio; Melemez, Kenan; Spinelli, Raffaele (Tubitak Scientific & Technological Research Council Turkey, 2015)
In contexts in which mechanized harvesting is limited, such as in the northwestern Black Sea region of Turkey, it is important to improve timber harvesting productivity while preserving operators' safety and reducing environmental damage. This study aims to introduce a methodology in which the harvesting process is simulated with discrete-event simulation (DES) software in order to identify bottlenecks. An alternative process is compared to the original within the DES software, carrying out further steps oriented to the generation of new innovative product concepts. As a case study, the design of an innovative skidding winch is proposed. The development of the product was focused towards customer satisfaction by collecting customer requirements and identifying quality characteristics with a quality function deployment approach. Contradictions identified in the design phase were solved using the TRIZ contradiction toolkit, generating different product concepts. Inventive solutions provided by TRIZ were designed within parametric CAD software. The concepts were compared in a virtual environment, eventually selecting an optimal solution. The results showed that, with the concept adopted, it is possible to achieve a substantial increase in productivity, from 121% to 133%, in terms of kilograms of logs per hour deposited on the landing.
Simulation of forest harvesting alternative processes and concept design of an innovative skidding winch focused on productivity improvement
Keywords: Discrete-Event Simulation; Forest Harvesting; Quality Function Deployment; Triz